2018
DOI: 10.7759/cureus.2988
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Transluminal Angioplasty with Stent Placement versus Best Medical Therapy Alone in Symptomatic Intracranial Arterial Stenosis: A Best Evidence Review

Abstract: Intracranial arterial stenosis (ICAS) is a common cause of stroke, and the risk of ischemic stroke from a stenotic intracranial artery remains high despite best medical therapy (BMT). As a result, clinicians have increasingly turned to percutaneous transluminal angioplasty and stenting (PTAS) over the last decade as an alternative therapy in high-risk patients with symptomatic ICAS. In this review, we will critically analyze multiple clinical trials to assess the safety and efficacy of PTAS with BMT versus BMT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…[ 46 , 47 ] with promising results and was only revisited in 2018 [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. However, despite good results and reviews continuing to advocate for the evaluation of DCB in the treatment and prevention of ECAS and ICAS in in-stent restenosis [ 57 , 58 , 59 ] and restenosis, data addressing the use of DCB and the evaluation of its possible benefits in the neurovascular setting remain rare; consequently, we believe that this field is under-investigated, and publications are lacking.…”
Section: Resultsmentioning
confidence: 99%
“…[ 46 , 47 ] with promising results and was only revisited in 2018 [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. However, despite good results and reviews continuing to advocate for the evaluation of DCB in the treatment and prevention of ECAS and ICAS in in-stent restenosis [ 57 , 58 , 59 ] and restenosis, data addressing the use of DCB and the evaluation of its possible benefits in the neurovascular setting remain rare; consequently, we believe that this field is under-investigated, and publications are lacking.…”
Section: Resultsmentioning
confidence: 99%
“…[31][32] The current studies and guidelines do not support the percutaneous intracranial stenting and EC-IC employed as first-line treatment in patients with ICAS. 7,33 Therefore, it is reasonable to use the drug strategy to improve the cerebral hypoperfusion in the patients who are unfit for the surgical revascularization. This study expands the upper limit of eligible age to 85 years old and does not exclude the above high-risk conditions for the surgical revascularization as possible as we can.…”
Section: Discussionmentioning
confidence: 99%
“…However, Stenting and Aggressive Medical Management for Prevention of Recurrent Stroke in Intracranial Stenosis (SAMMPRIS) investigators found that patients undergoing PTAS plus BMT for high-grade intracranial atherosclerosis have a significantly increased rate of recurrent stroke and death than patients receiving BMT alone (13). In a recent review, Padalia et al concluded that PTAS should only be considered in symptomatic ICAS patients that are hemodynamically unstable or have repeatedly failed BMT (18). Moreover, a recent study suggested that DCB is a viable alternative to drug-eluting stents, and the new advent of Neuro Elutax DCB further increased the feasibility of using DCB in intracranial arteries (19).…”
Section: Discussionmentioning
confidence: 99%